Extraction of Flavonoid Compounds from Red Betel (Piper crocatum) Using Ultrasound-Assisted Extraction (UAE) Method - Riavinola Viyoni Pramudiska; Audi Nur Amartya; Ditta Kharisma Yolanda Putri; Zuhriah Mumtazah; Bekti Palupi (University of Jember, 2023)
Piper crolatum or red betel is one of the medicinal plants known for its beneficial antioxidant content in maintaining overall health. One of the types of antioxidants found in red betel leaf is flavonoids. In this study, red betel leaf was extracted using the Ultrasound-Assisted Extraction (UAE) method to analyze the flavonoid content and antioxidant activity in the red betel leaf. A 90% ethanol solvent was used, and the extraction variables included the ratio of material to solvent, particle size, and extraction time, which were determined using Design Expert 13 software. The flavonoid test was performed using a UV-Vis spectrophotometer at 431 nm. The analysis of antioxidant activity was conducted using DPPH (2,2-Diphenyl-1-picrylhydrazyl). The highest flavonoid content obtained was 263.676 mgQE/g under the optimum operating conditions with a particle size of 100 mesh, a material-to-solvent ratio of 0.06, and an extraction time of 25 minutes.